2003
DOI: 10.1016/s0022-5223(03)01026-2
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged donor ischemic time does not adversely affect long-term survival in adult patients undergoing cardiac transplantation

Abstract: Prolonged donor ischemic time is not a risk factor for decreased long-term survival. Procurement of hearts with prolonged donor ischemic time is justified in the setting of an increasing recipient pool with a fixed donor population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 19 publications
3
46
0
4
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] Current donor and recipient criteria limit the use of hearts to donors who are within approximately 20% of the recipient's weight or a DR weight ratio of 0.8 to 1.2. Previous studies analyzing the impact of donor-to-recipient size have done so from an institutional perspective or as a subanalysis of a larger study.…”
Section: Patel Et Al Dr Weight Ratio and Htx S85mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] Current donor and recipient criteria limit the use of hearts to donors who are within approximately 20% of the recipient's weight or a DR weight ratio of 0.8 to 1.2. Previous studies analyzing the impact of donor-to-recipient size have done so from an institutional perspective or as a subanalysis of a larger study.…”
Section: Patel Et Al Dr Weight Ratio and Htx S85mentioning
confidence: 99%
“…1 Because of the donor organ deficit, efforts have been made to use marginal donors in an attempt to increase the donor organ pool and reduce waiting list mortality. [2][3][4][5][6][7] These attempts include the use of hearts from older donors 8 -11 and hearts that have been subjected to longer ischemic times, [12][13][14][15][16] both of which have led to conflicting results in the literature.…”
mentioning
confidence: 99%
“…Earlier reports have concluded that prolonged cold ischemic time is not a risk factor for decreased long-term survival in cardiac allograft recipients (Morgan et al, 2003), yet more recent studies have indicated that it is a predictor of a 5-year conditional mortality (Taylor et al, 2008). The effect of cold ischemic time on survival after heart transplantation is dependent on donor age, with greater tolerance among grafts from younger donors (Russo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Several studies have also reported reduced survival rates in patients with prolonged donor ischemic time, [4,6,[9][10][11] but other studies have not shown any connection. [1,12,13] Kilic et al [11] studied 9,404 patients who underwent an orthotopic heart transplantation from 1987 to 1999 and concluded that younger patient age (<55 years), a shorter donor ischemic time, and younger donor age were the most important factors for predicting the 10-year survival rate after cardiac transplantation. In addition, they also concluded that being Caucasian was also a significant factor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the diminishing number of brain death cases, a reduction of organ donations because of ethical or religious considerations has given rise to a decrease in local donor heart pools, so heart transplantation teams have started to harvest donor organs from more distant locations thanks to improvements in donor heart preservation methods that permit prolonged storage and the remote procurement of cardiac allografts. [1] As long as there are favorable survival rates for the recipients with allografts transplanted from far outside the generally accepted boundaries of donor age and ischemic time, transplantation teams will necessarily stretch the limits on the criteria for donor hearts. In the present study, we evaluated the effects of donor ischemic time and age on longterm mortality among patients who underwent heart transplantation in our clinic.…”
mentioning
confidence: 99%